Efektivitas Model Pembelajaran Berbasis Masalah dalam Meningkatkan Pemahaman Konsep Matematis dan Disposisi Matematis Siswa - Ria Noviana; Moh Supratman; Helmi Rahmawati (Universitas Qamarul Huda Badaruddin, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in improving students' mathematical conceptual understanding and mathematical disposition. The research employed an experimental design with a quantitative approach. The sample consisted of 38 eighth-grade students of SMP IP Darul Hukumaini, comprising 20 students in the experimental group and 18 in the control group. Research instruments included a mathematical conceptual understanding test and a mathematical disposition questionnaire. Data analysis involved validity testing, reliability, normality test, and t-tests. Findings revealed a significant improvement in the experimental group’s conceptual understanding, with higher posttest scores compared to pretest (t = 8.09 > 2.09). However, no significant difference was found between the experimental and control groups’ posttest results (t = 0.245 < 2.03). Students’ mathematical disposition also showed positive improvement through PBL. These findings highlight that PBL is effective in enhancing both cognitive and affective aspects, although its implementation should be supported by further strategies for optimal outcomes.